Efektivitas Penerapan Program K3LLP pada Kawasan Pengeboran Sumur Parang II Sepanjang Pandemik Covid-19 - Tatan Sukwika; Fredy Riwayando (LPPM Institut Teknologi Petroleum Balongan, 2022)
During the Covid-19 pandemic, health, work safety, environmental protection and security (K3LLP) conditions in the Parang II well drilling area became a big problem. Business activities were limited, resulting in a decline in demand in the global oil market. This study aims to examine the effectiveness of K3LLP risk management in drilling the Parang II well during the covid 19 pandemic. The research method is a survey method using a questionnaire. A sample of 67 people includes permanent workers, contracts, and contractors involved in drilling projects, both at the supervisory level and field leaders. Data analysis used regression analysis. The results show that K3LLP risk management is effective with a significant contribution value. In conclusion, the implementation of K3LLP risk management is well and effectively. Therefore, the managerial implications need adjustments based on ISO standards such as ISO 9001, ISO 14001, ISO 45001 and ISO 31000.